2017
DOI: 10.1371/journal.pone.0170387
|View full text |Cite
|
Sign up to set email alerts
|

Delaying rewards has greater effect on altruism when the beneficiary is socially distant

Abstract: Based on the assumption that social distance and time are dimensions of psychological distance important for altruistic choices it was predicted that enhancement of altruism due to delaying rewards when choosing between a reward for oneself and for another person would be more pronounced the greater the social distance between the subject and another person. In order to test this hypothesis, social discounting using hypothetical monetary rewards and manipulation of social distance and reward delay was measured… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 17 publications
1
4
0
Order By: Relevance
“…As a result, we can expect that delaying rewards when the choice is between a reward for oneself and one for another person enhances altruism and the extent of that enhancement is dependent on social distance between the subject and the other person. This expectation was confirmed empirically (Osiński and Karbowski, 2017), and this shows that the conceptualisation of the issue of relation between selfcontrol and altruism, as outlined in this paper, can be useful.…”
Section: Psychological Distancesupporting
confidence: 71%
See 1 more Smart Citation
“…As a result, we can expect that delaying rewards when the choice is between a reward for oneself and one for another person enhances altruism and the extent of that enhancement is dependent on social distance between the subject and the other person. This expectation was confirmed empirically (Osiński and Karbowski, 2017), and this shows that the conceptualisation of the issue of relation between selfcontrol and altruism, as outlined in this paper, can be useful.…”
Section: Psychological Distancesupporting
confidence: 71%
“…For instance, the fact that a delay of reward reduces the rate of social discounting and this happens pro rata to the distance between the subject and the beneficiary (Osiński and Karbowski, 2017) begs the question about the importance of the self-control level in this process. Based on the idea of "extended self", presented by Rachlin and Locey (2011), we could expect that giving up the reward for oneself should be less problematic for people who do not see a relation between their "present self" and "future self", namely people characterized by fast delay discounting.…”
Section: Discussionmentioning
confidence: 99%
“…In the psychological field, some social-discounting-focused studies have investigated transitions in the subjective value of others’ resources in the future 16 . Osiński and Karbowski 17 revealed that the relative value of the resources of socially distant others slightly increases in the future. This is consistent with our results.…”
Section: Discussionmentioning
confidence: 99%
“…This can lead people to make more altruistic decisions. Studies on social discounting—in which people discount others’ resource values compared to their own resources—indicate that the discount rate becomes smaller in the distant future 16 , 17 . Although this is consistent with the prediction from the construal level theory, it is unclear what type of altruistic preference is facilitated by future thinking (i.e., temporal distance).…”
Section: Introductionmentioning
confidence: 99%
“…However, Yang and Carlsson [21] find that individual decisions are similar to joint decisions in terms of time preferences. Another group of works examine time preferences and social preferences, finding that more patient subjects are likely to share payoffs with other people in social-dilemma situations [3,22,23]. Ambrus et al, and He and Villeval [24,25] demonstrate that a "median" member (who has a median social preference in a group) has a significant influence on group decisions since the highest and the lowest members tend to be attracted to the median.…”
Section: Introductionmentioning
confidence: 99%